Graphic modeling of emerging phenomenon: A prospective need - Enault, Laure Casanova; Chatel, Cathy [UNESP] (My University, 2017)
The graphic modeling of prospective scenarios developed under the Sustainable Territory 2030 program - developed by the Ministry of Ecology, Sustainable Development and Energy - offered an opportunity to examine the adjustment of the method to the needs of prospective representation. The challenge was to experiment new ways to represent two topics that are diffi cult to grasp with the method; but which have become decisive in the understanding of territorial evolution due to the generalization of the reference base for sustainable development: the environment and governance.
Modelización gráfica de fenómenos emergentes: una necesidad para la prospectiva
La modélisation graphique de phénomènes émergents pour répondre aux besoins de la prospective
Keywords: Environment; Governance; Graphic modeling; Prospective